ICHTHYOFAUNAL SURVEY OF SOME FRESH WATER RESERVOIRS IN PUNJAB - A. M. Khan; H. A. Shakir; M. N. Khan; M. Abid; M. R. Mirza (Journal of Animal and Plant Sciences, 2008)
Present study was conducted to analyze the overall status of ichthyofauna at Chashma (River Jhelum) and Taunsa (River Indus) freshwater reservoirs. Fish catches were overall dominated by native fishes along with exotic fishes like Ctenopharyngodon idella, Hypopthalmichthys molitrix, Hypopthalmichthys nobilis, Cyprinus carpio, Carassius auratus, Oreochromis aureus, Oreochromis mossambicus, and Gambusia affinis. Statistically values for richness was significantly high in the months of September and October for both the reservoirs, however diversity and evenness were comparable at both the reservoirs. carps have been found in three provinces in Pakistan:
Keywords: Fish fauna; Freshwater; Taunsa; Chashma; Punjab